Narrative Gamification as a Method of Increasing Sales Performance: A Field Experimental Study - Grobelny, Jaroslaw; Smierzchalska, Joanna; Czapkowski, Krzysztof (My University, 2018)
There is ongoing dispute whether gamification is an effective tool in increasing sales performance. Furthermore, there is a lack of evidence of gamification being a job performance management tool. After the discussion of elements of gamification (with a focus on narration) and the mechanism of this procedure, a field study was conducted to investigate whether implementing narrative gamification within a company will increase sales performance. The study involved 81 employees of two comparable franchise units. Over a period of two months, in one franchisee the employees were working on their regular basis, while narrative gamification took place in the second franchisee. The basic measures were the sales volume data and sales change rates of the two telecommunications products. Tests for difference and effect size were employed. The results of the intervention conducted have shown that narrative gamification had a positive impact on sales performance after two months. Not only did the sales performance in the gamified franchisee increase, but the increase exceeded that of the other franchisee.
Keywords: Gamification; Performance Management; Job Performance; Motivation; Work Engagement